Characterization of putative haematopoietic cells from bovine yolk sac. (25th February 2015) - Oliveira, Vanessa C.; Mançanares, Celina A. F.; Oliveira, Lilian J.; Gonçalves, Natalia J. N.; Miglino, Maria A.; Perecin, Felipe; Meirelles, Flávio V.; Piedrahita, Jorge; Ambrósio, Carlos E.
Abstract: The yolk sac is an extra‐embryonic membrane that plays an important role in early embryonic survival. It is the production site for blood cells during embryonic mammalian development and is a likely source of stem cells. The aim of this study was to identify and characterize the putative haematopoietic cells from the yolk sac of bovine embryos at different stages of gestation. The yolk sac regresses according to gestational age and embryos are characterized into groups (I–V) according to the crown–rump measurement. Groups I–III survived in culture longer and exhibited the formation of cell clusters, whereas groups IV and V could not be maintained in culture for an extended period of time. Flow‐cytometry analysis revealed that groups I–III had similar characteristics, including high expression levels of the haematopoietic markers CD34, CD90 and CD117. In groups IV and V, decreases were observed in the expression levels of CD117 and CD34. Cells were found to be capable of survival post‐cryopreservation and exhibited varying abilities to form colonies in a methylcellulose matrix, depending on gestational age. Cytological analysis revealed the presence of blood cells (lymphocytes and monocytes). Quantitative PCR analysis demonstrated the presence of the haematopoietic progenitor genes GATA3 and LMO2, but not RUNX1 . Thus, we have successfully isolated and characterized haematopoietic cells from the bovine embryo yolk sac at varying gestational ages. This study is crucial for the understanding of the development of the haematopoietic system and the embryonic function of this organ. Copyright © 2015 John Wiley & Sons, Ltd.